Impact of typhoon Soudelor on ozone and water vapor in the Asian monsoon anticyclone western Pacific mode - Dan Li; Jianchun Bian; Xin Zhang; Bärbel Vogel; Rolf Müller; Gebhard Günther (Atmospheric Science Letters, 2023)
Abstract Ozonesonde measurements from Hong Kong and Naha are combined with satellite observations to investigate the vertical structure of ozone and water vapor around the tropopause during typhoon Soudelor over the northwestern Pacific in 2015. The results show that the tropopause height is decreased compared to the mean tropopause during 2000–2017 in the western Pacific mode of the Asian summer monsoon anticyclone (ASMA). The vertical transport associated with Soudelor decreases the ozone concentration by 60% in the upper troposphere. Further the equatorward transport from high latitudes around the western Pacific mode of the ASMA increases ozone concentration by 40% in the lower stratosphere. Cross‐tropopause transport of water is observed above typhoon Soudelor, and water vapor to be enhanced at 80–100 hPa compared to nontyphoon regions. Dehydration is observed below the tropopause around the eye of Soudelor.